Assessment of Corneal Biomechanical Properties and Intraocular Pressure in Myopic Spanish Healthy Population. (25th February 2014) - del Buey, María A.; Lavilla, Laura; Ascaso, Francisco J.; Lanchares, Elena; Huerva, Valentín; Cristóbal, José A.
Abstract : Purpose . To examine biomechanical parameters of the cornea in myopic eyes and their relationship with the degree of myopia in a western healthy population. Methods . Corneal hysteresis (CH), corneal resistance factor (CRF), Goldmann correlated intraocular pressure (IOP), and corneal compensated IOP (IOPcc) were measured using the ocular response analyzer (ORA) in 312 eyes of 177 Spanish subjects aged between 20 and 56 years. Refraction was expressed as spherical equivalent (SE), which ranged from 0 to −16.50 diopters (D) (mean: −3.88 ± 2.90  D). Subjects were divided into four groups according to their refractive status: group 1 or control group: emmetropia (- 0.50 ≤ S E < 0.50 ); group 2: low myopia (- 0.75 ≤ S E < 3.00  D); group 3: moderate myopia (- 3.00 ≤ S E ≤ - 6.00  D); and group 3: high myopia (SE greater than −6.00 D). We analyzed the relationship between corneal biomechanics measured with ORA and SE. Results . CH in the emmetropia, low myopia, moderate myopia, and high myopia groups was 11.13 ± 0.98, 11.49 ± 1.25, 10.52 ± 1.54, and 10.35 ± 1.33  mmHg, respectively. CH in the highly myopic group was significantly lower than that in the emmetropic group (P = 0.07 ) and low myopic group (P = 0.035 ); however, there were no differences with the moderate myopic group (P = 0.872 ). There were no statistically significant differences regarding IOP among the four groups (P > 0.05 ); nevertheless, IOPcc was significantly higher in the moderately myopic (15.47 ± 2.47  mmHg) and highly myopic (16.14 ± 2.59  mmHg) groups than in the emmetropia (15.15 ± 2.06  mmHg) and low myopia groups (14.53 ± 2.37  mmHg). No correlation between age and the measured parameters was found. CH and IOPcc were weakly but significantly correlated with SE (r = 0.171, P = 0.002 and r = - 0.131, P = 0.021, resp.). Conclusions . Present study showed only a very weak, but significant, correlation between CH and refractive error, with CH being lower in both moderately and highly myopic eyes than that in the emmetropic and low myopic eyes. These changes in biomechanical properties of the cornea may have an impact on IOP measurement, increasing the risk of glaucoma.